2018
DOI: 10.2147/ceor.s161299
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibiotic prescription in southern Italian outpatients: real-world data analysis of socioeconomic and sociodemographic variables at a municipality level

Abstract: PurposeThe aim of this study was to analyze the geographic variation in systemic antibiotic prescription at a regional level and to explore the influence of socioeconomic and sociodemographic variables.MethodsThis study was a retrospective analysis of reimbursement pharmacy records in the outpatient settings of Italy’s Campania Region in 2016. Standardized antibiotic prescription rates were calculated at municipality and Local Health Unit (LHU) level. Antibiotic consumption was analyzed as defined daily doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 41 publications
(46 reference statements)
5
24
0
Order By: Relevance
“…It is worthwhile to underline that the proportion of individuals who reported having taken at least one antibiotic for himself/herself (47.9%) or for their minor son/daughter (55.4%) in the previous 12 months is among the highest reported in European Member States, emphasizing that antibiotic consumption is considerable in the study area as well as in the country as a whole [ 29 ]. A similar antibiotic consumption prevalence (46.8%) was observed in a retrospective analysis of reimbursement pharmacy records in the outpatient setting of another Region of Southern Italy [ 28 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It is worthwhile to underline that the proportion of individuals who reported having taken at least one antibiotic for himself/herself (47.9%) or for their minor son/daughter (55.4%) in the previous 12 months is among the highest reported in European Member States, emphasizing that antibiotic consumption is considerable in the study area as well as in the country as a whole [ 29 ]. A similar antibiotic consumption prevalence (46.8%) was observed in a retrospective analysis of reimbursement pharmacy records in the outpatient setting of another Region of Southern Italy [ 28 ].…”
Section: Discussionsupporting
confidence: 72%
“…The results of multivariate analysis underlined the heterogeneity of public knowledge regarding antibiotics and AMR on the basis of sociodemographic factors. These figures could be helpful as a considerable inter- and intraregional variability in antibiotic consumption and prescribing pattern has been already described in Italy [ 27 ] as well as its relationship with sociodemographic factors [ 28 ]. Our findings indicated that males, foreign nationals and those with a lower level of education had poor knowledge of antibiotics and AMR and could be highly useful in planning tailored educational interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study concluded that higher prevalence rates were related to urban municipalities and low average annual income levels. 16 In our study, we observed a statistically significant correlation of rank distributions of prevalence rates at municipality level between children, adults, and the older adults. Different factors may explain these geographical differences observed in all three groups, such as socio-cultural, demographic, economic determinants, as well as different prescribing attitudes between physicians.…”
Section: Discussionsupporting
confidence: 53%
“…15 According to earlier estimates of a recent study, in this region, there is a strong relationship between antibiotic prevalence rates and sociodemographic and socioeconomic factors at a municipality level. 16 Nevertheless, this work did not analyze prescriptive patterns related to age, sex and type of class of antibiotic drugs. Reason why, the aims of the present study are to (a) analyze outpatient drug prescriptions records in Campania to describe patterns of antibiotic use by age and sex, and (b) estimate the distribution of prevalence prescription rates in children, adults, and the older adults ≥65 years at a municipality level.…”
Section: Introductionmentioning
confidence: 99%
“…The Campania Region Database (CaReDB) includes information on patient demographics, the electronic records of outpatient pharmacy dispensing and hospital discharges for ~6 million residents of a well-defined population in Italy (~10% of the population of Italy). CaReDB is complete and includes validated data in previous drug utilization studies [9][10][11][12][13][14][15][16][17]. The characteristics of CaReDB are described in S1 Table. From the beginning of the Covid-19 epidemic, a surveillance system was implemented to collect all cases identified by reverse transcription-polymerase chain reaction (RT-PCR) testing for SARS-CoV-2.…”
Section: Target Population and Data Sourcementioning
confidence: 99%